ANALISIS KESULITAN MURID DALAM MENGERJAKAN SOAL CERITA MATEMATIKA BERDASARKAN POLYA MATERI OPERASI HITUNG PADA BILANGAN CACAH KELAS V SDN 1 MRANTI - Fathin Hidayati; Nur Ngazizah; Rintis Rizkia Pangestika (STKIP Subang, 2025)
This study aims to analyze students' difficulties in solving mathematical word problems based on Polya's problem-solving steps in the topic of arithmetic operations on whole numbers for fifth-grade students at SDN 1 Mranti. This research employs a qualitative approach using a descriptive method. The research subjects consist of 23 fifth-grade students from SD Negeri 1 Mranti in the 2024/2025 academic year. Data collection techniques include written tests, interviews, documentation, and field notes. The collected data encompass difficulties in understanding the problem, difficulties in devising a plan, difficulties in carrying out the plan, and difficulties in reviewing the solution. Data analysis is conducted using triangulation techniques to obtain research results, which are then analyzed through data reduction, data presentation, and drawing conclusions. The results of observations and interviews indicate that students at SDN 1 Mranti face difficulties in understanding the problem, devising a plan, carrying out the plan, and reviewing the solution. Students struggle to identify key information and comprehend the context of word problems. In the planning stage, they have difficulty determining appropriate problem-solving strategies. The causes of these difficulties include a lack of basic conceptual understanding, low reading ability, and insufficient practice with word problems. Based on these findings, it is recommended that teachers implement Polya’s problem-solving strategies in a structured manner, increase practice with word problems, and provide support for students experiencing difficulties.